44.6k views
3 votes
Make x the subject of 5(x-3) = y(4-3x)

User Sint
by
5.7k points

2 Answers

4 votes

Answer:-

5(x-3)=y(4-3x)

5x-15=4y-3xy

5x+3xy=4y+15

x(5+3y)=4y+15

x=>(4y+15)/(5+3y)

:)

User WestAce
by
5.4k points
3 votes

Answer:

Explanation:

5(x - 3) = y(4 - 3x)

Use distributive property

5*x - 5*3 = y*4 - y*3x

5x - 15 = 4y - 3xy

5x = 4y -3xy + 15

5x + 3xy = 4y +15

x(5 + 3y) = 4y +15

x =
(4y+15)/(5+3y)

User Yajiv
by
4.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.